Design of the Digital I/O Pad Buffer for Mixed-Voltage Application - Said El Mouzouade; Karim El khadiri; Zakia Lakhliai; Ahmed Tahiri (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2021)
A new circuit design of digital bidirectional input/output (I/O) pad buffer for mixed voltage is presented. The digictal bidirectional I/0 buffer is designed to avoid reflections by matching the output impedance to the 50 ohms of the transmission line and having overshoots and undershoots below 300mV by increasing the output impedance. The digital bidirectional I/O pad buffer provides minimum delays between input and output and minimum rising and falling times. The proposed digital bidirectional I/O pad buffer was designed, simulated and layouted in Cadence using in TSMC  0.18um CMOS process with a linear resistive element electrically connected at an I/O pad for limiting a processed data I/O signal. The output rising time and falling time are 0.42 ns and 0.93 ns with 3pF load respectively. The final chip area is only 5 um2 .